The Work of Wind : Land - Shaw, Christine; Turpin, Etienne; Springer, Anna-Sophie; Malecki, Jeffrey (Berlin : K. Verlag, 2018)
Akhbari, Rouzbeh ; d'bi.young anitafrika ; Van Balen, Tuur ; Balkin, Amy ; Birch, Jesse ; Cochrane, D. T. ; Revital Cohen ; Feigenbaum, Anna ; Gómez-Barris, Macarena ; Halperin, Ilana ; Kalmenson, Felix ; Keefer, Tom ; Marcel, Barbara ; Onuoha, Mimi ; Saraceno, Tomás ; Shaw, Christine ; Spahr, Juliana ; Telford, Adrienne ; Turpin, Etienne ; Weiss, Allen S. ; Willard, Tania ; Wilson, Eva
HE WORK OF WIND: AIR, LAND, SEA project series aims to foster a deeper public awareness of the complex entanglements of ecologies of excess, environmental legacies of colonialism, the financialization of weather, contemporary catastrophism, politics of sustainability, climate justice, and hopeful resilience. Across a variegated set of curatorial and editorial instantiations, the Beaufort Scale of Wind Force will become a diagram of prediction and premonition in the context of our accelerating planetary extinction. While the title might suggest a weather project, it is not about wind but of wind, of the forces of composition and decomposition predicated on extraction, dispossession, accumulation, and infrastructure. (provided by publisher)
The Work of Wind: Air, Land, Sea, a variegated set of curatorial and editorial instantiations of the Beaufort Scale of Wind Force, developed by Christine Shaw from June 2018 to September 2019
boek